2014
DOI: 10.1007/s40271-014-0081-0
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Benefits and Risks of Emerging Treatments for Idiopathic Pulmonary Fibrosis: A Qualitative Study

Abstract: In identifying issues associated with emerging IPF treatments, we demonstrate the value of qualitative research in understanding the views of diverse stakeholders and in providing a basis for future survey research. As such, qualitative methods should play an important role in understanding the benefits and risks of emerging therapies and in promoting patient-centered drug development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…They discussed issues of paucity of scientific data and the need to balance risks and benefits. Bridges et al [7] pick up this theme in their paper about patients with idiopathic pulmonary fibrosis. Analysis of interviews with patients, researchers and policy/industry informants showed that patients seemed to understand issues relating to emerging treatments.…”
Section: Attitudes To New Medicinesmentioning
confidence: 99%
“…They discussed issues of paucity of scientific data and the need to balance risks and benefits. Bridges et al [7] pick up this theme in their paper about patients with idiopathic pulmonary fibrosis. Analysis of interviews with patients, researchers and policy/industry informants showed that patients seemed to understand issues relating to emerging treatments.…”
Section: Attitudes To New Medicinesmentioning
confidence: 99%
“…Moreover, then the question arises of which patient organization to involve. A potential solution to address these issues might be, as suggested by some interviewees and several authors ( 10 , 17 , 27 , 31 , 33 , 34 , 36 , 38 42 ), the use of evidence from (quantitative) patient preference studies, by which patient preferences are being measured from a group of patients. To decide whether the input from disease-specific or umbrella patient organizations is needed, the authors propose to address this problem bottom-up, via looking at what type of patient information is needed per decision.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, potential side effects of these drugs need to be balanced with the treatment effect [ 33 , 34 ]. Evaluation of patient experiences can thus play a significant role when considering treatment approaches [ 35 , 36 ]. In The Netherlands, it is estimated that between 800 and 1600 people are diagnosed with IPF each year [ 37 ].…”
Section: Conceptual Model and Contextmentioning
confidence: 99%